Code of Conduct: Teachers and the Ethics of AI in Humanities Education - Deshmukh, Sneha (International Journal of Psychosocial Rehabilitation, 2025)
The increasing presence of artificial intelligence (AI) in education, particularly in the humanities, presents a complex mix of opportunities and challenges. The current study’s research literature outlines the importance of personalised learning, predictive models, intelligent robots, and automated assessment for education by reviewing research literature. Such technology plays an important role for teachers. In this paper, a qualitative survey is conducted involving teachers. The study aims to evaluate the insights from the teachers for the use of AI in education. The results show that teachers quickly adapt to the reality of Aassisted learning and that educators are aware of and open to such technologies, despite generation and discipline, to use them as a teaching tool. This shows positive results because the digital world should be advantageous for students to find their way to the learning process to keep them attractive. Teachers’ communication and their collaboration with students are important for the best use of digital technology for effective education. The teacher’s professional development depends on extensive prospects that outline the intentional technologies for specific skills cooperation. Studies conclude that these techniques and their proper use, teachers are important for students, and that effective education in a time of artificial intelligence has better results.